The multiplicity of scripture the making of the Antwerp polyglot Bible - Dunkelgrün, Theodor 1976- (PIMS, Pontifical Institute of Mediaeval Studies, 2025)
The Antwerp Polyglot Bible (1568-1573) was one of the most ambitious typographical enterprises of the sixteenth century, with editions of the ancient Hebrew, Aramaic, Syriac, Greek, and Latin versions together with new scholarly instruments necessary to study and compare them -- yet powerful contemporaries also perceived it as a threat to the Church. The Multiplicity of Scripture is the first book-length study of how the Antwerp Polyglot was made. Combining the history of the book with the history of scholarship and drawing on primary sources from archives and libraries across Europe, it reconstructs the editorial history of Christopher Plantin's masterpiece, telling a story of crisis and craftsmanship, of ink-stained proofs in four different alphabets, and of the extraordinary team of scholars and printers that created this monument of Renaissance printing and scholarly endeavour